Torsion of huge cystic teratoma of ovary with multiple fibroids uterus: a case report and review of literature - Katke, Rajshree D. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Ovarian teratomas and leimyomas are tumours of reproductive age group. But simultaneous occurrence of these tomours is rare. Here we present a rare case of benign cystic teratoma which underwent torsion along with multiple uterine fibroids.